2013
DOI: 10.4142/jvs.2013.14.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of virulent pseudorabies virus infection in Northern China

Abstract: Our investigation was conducted in order to verify a recent severe epidemic at several swine farms in northern China that indicated a newly emerging disease. Evidence confirmed that the epidemic was caused by a virulent Pseudorabies virus infection in swine herds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 4 publications
6
113
0
1
Order By: Relevance
“…This suggested that the PR vaccine was not effective against wild-type PR infection. According to recent studies, the causative agent of the outbreak was a PRV variant that showed enhanced pathogenicity [3,7,8,10]. In the present study, the PRV strain SH2012 was isolated in 2012 from an infected pig farm in Shanghai, China that used the typical vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that the PR vaccine was not effective against wild-type PR infection. According to recent studies, the causative agent of the outbreak was a PRV variant that showed enhanced pathogenicity [3,7,8,10]. In the present study, the PRV strain SH2012 was isolated in 2012 from an infected pig farm in Shanghai, China that used the typical vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The causative agent of the outbreaks was confirmed to be a PRV variant [3,9]. The PRV variant was shown to be both antigenically different from the classical PRVs and more pathogenic in older pigs [3,7,8,10]. Previous studies on immunological protection in sheep have shown that the Bartha-K61 vaccine does not provide complete protection against the emerging PRV variant, but could offer full protection against infection with PRV strain SC (an earlier virulent strain in China) [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 PRV continues to spread worldwide, especially among some countries in South America, Europe, and Asia, while others, including Germany, Sweden, Denmark, and England, have eradicated PR. The United States, France, Poland, and other countries have eradicated PR among domestic pig populations (Lipowski A, Pejsak Z, Antibody prevalence of pseudorabies virus in feral pigs in Poland, In: Proceedings of 17th International Pig Veterinary Society Congress, 2002;2:223).…”
mentioning
confidence: 99%
“…Black triangles show cities with seropositive samples. Original image: (Wu et al 2013) direction) makes it a useful live neural tracer and activity reporter (Boldogkoi et al 2009), further extending its research value.…”
Section: Introductionmentioning
confidence: 99%